The Rochester Epidemiology Project: exploiting the capabilities for population-based research in rheumatic diseases - Kremers, Hilal Maradit (Oxford University Press, 2011)
The Rochester Epidemiology Project (REP) is a patient record-based database based upon a medical records-linkage system for all residents of the Olmsted County, MN, USA. This comprehensive system includes all health-care providers of patients resident in this geographically defined region. It uniquely enables long-term population-based studies of all medical conditions occurring in this population; their incidence and prevalence; permits examination of disease risk and protective factors, health resource utilization and cost as well as translational studies in rheumatic diseases.